Survey of Coal Stock Opname Using Terrestrial Method at PT Lamindo Inter Multikon, Bunyu Site - Taufik, Muhammad; Syafi'i, Ahmad Ali; Hakim, Romla Noor (Jurnal Himasapta, 2025)
The mining industry's coal stock opname survey is a crucial process to ensure inventory data accuracy. This study observes the application of the terrestrial survey method in measuring coal stockpiles at PT Lamindo Inter Multikon, Bunyu Site, North Kalimantan. Data collection was conducted using a Total Station, which was then processed using SURPAC software to generate a Digital Terrain Model (DTM) and calculate the stockpile volume. The survey results were compared with weighbridge data to assess volume discrepancies. The findings showed that the stockpile volume was 71,161.918 m³, with a weight of 64,045.7262 tons. However, a comparison with weighbridge data revealed a discrepancy of 7,916.27 tons or 12.36%, exceeding the tolerance limit recommended in good mining practices. Factors contributing to this discrepancy include the moisture condition of the coal at the time of weighing and differences in the basement model used in DTM calculations. Therefore, improving the accuracy of basement data collection and implementing supporting infrastructure to minimize the impact of moisture on coal weight is necessary.